Assessment of Satellite-Derived FAPAR Products With Different Spatial Resolutions for Gross Primary Productivity Estimation - Xiyu Zhang; Huaan Jin; Wei Zhao; Gaofei Yin; Xinyao Xie; Jianrong Fan (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Accurate estimation of gross primary productivity (GPP) is crucial for understanding terrestrial carbon cycles and assessing ecosystem health. Light use efficiency (LUE) models, which are widely used for the generation of regional or global GPP products, often rely on the fraction of absorbed photosynthetically active radiation (FAPAR). However, most of the existing FAPAR products with moderate to coarse spatial resolutions introduce uncertainties in GPP estimations across heterogeneous landscapes. In this work, the MODerate resolution Imaging Spectroradiometer (MODIS) FAPAR product at the 500-m resolution, along with a new HIgh-spatial-resolution Global LAnd Surface Satellite (Hi-GLASS) FAPAR dataset at the 30-m resolution, was used to drive an LUE model for GPP estimations at 188 eddy covariance (EC) sites. Then, they were compared and evaluated based on the EC GPP measurements. Results showed that Hi-GLASS FAPAR provided the GPP estimates with more detailed spatial information compared with MODIS FAPAR. Moreover, Hi-GLASS FAPAR significantly improved GPP estimations, with an overall R2 increase from 0.54 (MODIS) to 0.63 (Hi-GLASS) and a root-mean-square error (RMSE) decrease from 3.04 to 2.70 gC⋅m−2⋅day−1. In addition, 75% of the selected sites exhibited enhanced R2 values with Hi-GLASS FAPAR, demonstrating its application potential in GPP estimations across different vegetation types. Specifically, crop sites exhibited the most notable improvements, with an R2 increase of 0.16 and an RMSE decrease of 0.70 gC⋅m−2⋅day−1. These findings highlight the advantages of high-resolution FAPAR data in capturing spatial heterogeneity and improving the accuracy of GPP estimations and underscore its potential for refined ecosystem monitoring.